On the optimal design of forward osmosis desalination systems with NH3–CO2–H2O solutions. Issue 5 (28th June 2017) - Gazzani, Matteo; Hartmann, Thomas; Pérez-Calvo, José-Francisco; Sutter, Daniel; Mazzotti, Marco
Abstract : The optimal working pressure and composition of the draw solution is identified. The forward osmosis process is compared with reverse osmosis and thermal desalination in terms of specific work, membrane area, and second law efficiency. Abstract : Membrane-based forward osmosis, especially when NH3 –CO2 –H2 O mixtures are adopted as draw solutions, is a promising new process for clean water production, including seawater desalination and wastewater treatment. In such a process, water is first removed from the feed ( e.g. seawater) by exploiting the osmotic pressure difference between the feed and the draw solution, which are at the two sides of the membrane; in a second step, drinkable water is produced by treating the water-rich draw solution in a distillation column. Accordingly, the main energy requirement is thermal energy for the reboiler. In order to enable a robust performance evaluation of forward osmosis systems, developing a comprehensive simulation framework that couples a rigorous distillation model and a reliable thermodynamic model for electrolyte solutions with an optimization routine is needed. With this work, we aim at satisfying this need by providing (i) a comprehensive analysis of forward osmosis-based systems, with special emphasis on the recovery of the draw solution and the connected energy demand, and (ii) a systematic approach to the design and operation of such processes. Ternary phase diagrams of NH3 –CO2 –H2 O are used to characterize the system in terms of osmotic pressure, thermal separation energy and pressure in the distillation column. An optimization routine is then developed to minimize the equivalent energy and the membrane area specific to the water produced: different Pareto curves along with the associated trends in the design variables are identified and explained. Finally, forward osmosis is compared to reverse osmosis and thermal desalination plants.